2023
DOI: 10.3390/ijms24054578
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Investigation of the NAC Transcription Factor Family in Apocynum venetum Revealed Their Synergistic Roles in Abiotic Stress Response and Trehalose Metabolism

Abstract: NAC (NAM, ATAF1/2, and CUC2) transcription factors (TFs) are one of the most prominent plant-specific TF families and play essential roles in plant growth, development and adaptation to abiotic stress. Although the NAC gene family has been extensively characterized in many species, systematic analysis is still relatively lacking in Apocynum venetum (A. venetum). In this study, 74 AvNAC proteins were identified from the A. venetum genome and were classified into 16 subgroups. This classification was consistentl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 71 publications
0
7
0
Order By: Relevance
“…Transcription factors (TFs) control plant metabolism, germination, and responses to biotic and abiotic stressors [ 22 , 23 ]. In our study, 605 differentially expressed TFs were annotated to the transcriptome of F. thunbergii , which was divided into 33 transcription factor families.…”
Section: Resultsmentioning
confidence: 99%
“…Transcription factors (TFs) control plant metabolism, germination, and responses to biotic and abiotic stressors [ 22 , 23 ]. In our study, 605 differentially expressed TFs were annotated to the transcriptome of F. thunbergii , which was divided into 33 transcription factor families.…”
Section: Resultsmentioning
confidence: 99%
“…Trehalose plays a crucial role in protecting cells and organisms from various stresses and it acts as a stabilizer to help organisms survive unfavorable conditions by stabilizing proteins, membranes, and cellular structures [ 51 , 59 ]. Previous studies have shown that many transcription factors can enhance salt tolerance in plants by increasing the trehalose content [ 60 , 61 , 62 , 63 ]. Trehalose biosynthesis had been intensively investigated in plants and has been found to include two steps: the first step involves trehalose-6-phosphate (TPS), which transfers glucose from UDP-glucose to trehalose-6-phosphate and then synthesizes trehalose [ 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…The widespread availability of plant genomes [39] enables the systematic characterization of predicted genic features in terms of their functional and phenotypic correlates. Within this exciting framework, Huang et al [31] achieved in silico prediction of the role of NAC transcription factors (TFs) to face a wide spectrum of abiotic stresses [40], including drought and salinity, among others [41], in Apocynum venetum (Apocynaceae), an important source of natural fiber, ideally as restoration species for saline-alkaline soils. Specifically, the authors offered a comprehensive analysis of the TFs involved in the abiotic stress response in these species.…”
Section: Polygenic Diversity For Abiotic Stress Tolerancementioning
confidence: 99%